New species of the genus Polyplectropus Ulmer 1905 (Insecta: Trichoptera: Polycentropodidae) from Indian Himalaya - Pandher, Manpreet Singh; Parey, Sajad Hussain (Zootaxa, 2018)
This paper is another contribution to the Indian caddisfly fauna of genus Polyplectropus Ulmer. Here, we describe and illustrate three new species of the genus from the Indian Himalaya: Polyplectropus sainii sp. nov. and Pol. himachalica sp. nov. (both from Himachal Pradesh) and Pol. kailashchandrai sp. nov. (from Uttarakhand). With these new additions, the genus is now represented by 7 species from India.